Meet Molly : an American girl - Tripp, Valerie, 1951-; Backes, Nick (Madison, Wis. : Pleasant Co., 1986)
While her father is away fighting in World War II, Molly finds her life full of change as she eats terrible vegetables from the victory garden and plans revenge on her brother for ruining her Halloween.
"1944"--Cover.
"Book one"--Cover.
740
Accelerated Reader AR
Keywords: Brothers and sisters -- Juvenile fiction; Halloween -- Juvenile fiction; World War, 1939-1945 -- United States -- Juvenile fiction